Reducing Cost and Contention of P2P Live Streaming through Locality and Piece Selection - Md. Shah, W.; Ishmael , J.; J.P. Race, N. (2011)
The use of locality within peer-to-peer (P2P) networks is ensuring the construction of overlay networks that are both economically viable for network operators and scalable. However, the underlying protocols on which traditional P2P overlays are based are rapidly having to evolve in order to better support more time sensitive, real-time video delivery systems. This shift places greater demand on locality mechanisms to ensure the correct balance between bandwidth savings and successful timely playback. In this paper, we investigate the impact of peer locality within live streaming P2P systems and consider the pertinent challenges when designing locality based algorithms to support efﬁcient P2P live streaming services. Based on our ﬁndings we propose an algorithm for supporting locality and harmonised play points in a live streaming P2P system. We present our results and in-depth analysis of its operation though a series of simulations which measure bandwidth consumption at network egress points, failure rates and each peer’s play point relative to the live stream.